An Analysis Of Stability Slope By The Use Of Bamboo As An Alternative Bracing (A Case Study: Road Area Grogol Semarang City ) - Bagus Ratna Saputra; Singgih Tri Hatmodjo (International Conference on Coastal and Delta Areas, 2017)
Landslides often occurs because caused by rain , earthquake , and the load that stands in an area of the slope . .then of it badly needed handling landslide effective and efficient , to danger due to landslide could be on tap . During this in handling landslide do with using a retaining wall of land, the plaster , and the installation of geotextile. In this research by the use of bamboo terucuk as bracing of slopes on urban Village Road Grogol Pudak Payung Semarang City it is hoped can increase the stability of a slope , the reeds are in use is bamboo a rope with a diameter of 15 cm and bamboo betung with a diameter of 25 cm. Analysis on the plaxis v.8.2 and geoslope. The results of the study showed that, 1) of a series of land test showed c = 37.265 kn/m2,  = 13º, γsat = 18.854 kn/m3, γunsat = 14.866 kn/m3. 2) bamboo data : ea bamboo petung = 7.31x105 kn/m, ei bamboo petung = 850.25 kn.m2, ea bamboo tali = 6.3x104, ei bamboo tali = 145.6 kn.m2. 3) the condition slope in the way of grogol unstable which the figures security the state of experience is sf = 1.4866, and after in give burden sf = 1.4856, after in give bracing of with the bamboo and analysis from safety factor is showed factors sf = 1,8339 where the was assumed safer if safety factor (sf) >1.5. Keywords: stability slope , bamboo petung , bamboo rope , security factor .